A Phase 2 Basket Trial of Ado-Trastuzumab Emtansine for Patients with HER2 Amplified Cancers: A Non-Randomized Clinical Trial - Jessica S. Ross; Winston Wong; Lauren Schoech; Alex Makhnin; Dazhi Liu; Ranieri Yllanes; Jonathan Loi; Ala'A Damrah; Amanda Johnson; Michelle S. Ginsberg; Vetri Sudar Jayaprakasam; Mark Dunphy; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: To evaluate the efficacy of ado-trastuzumab emtansine (T-DM1) among patients with advanced/metastatic HER2-amplified solid tumors. Patients and Methods: This was a single-center, non-randomized phase 2 basket trial conducted at Memorial Sloan Kettering Cancer Center. All 95 patients had HER2-amplified metastatic/advanced disease and were enrolled in 1 of 5 cohorts. HER2 amplification was diagnosed either with next-generation sequencing or in-situ hybridization. All patients received intravenous T-DM1 3.6 mg/kg every 21 days. The primary endpoint was overall response rate (ORR). Overall survival (OS), progression-free survival (PFS), duration of response (DOR), and safety were secondary endpoints. Results: We treated 95 patients, and 22 (23% [95% CI, 16–33%]) had a confirmed response by investigator assessment. The investigator-assessed confirmed ORRs by cohort were: salivary 11/19 (58% [95% CI, 36–77%]); lung 4/23 (17% [95% CI, 7–37%]); colorectal 0/7 (0% [95% CI, 0–35%]); endometrial 5/23 (22% [95% CI, 10–42%]); “other” 2/23 (9% [95% CI, 2–27%]). Median PFS was 3.6 months (95% CI, 2.6–5.4) and ranged from 1.4 months in the “other” cohort to 10.2 months in the salivary cohort. Median OS was 11.9 months (95% CI, 8.4–17.2) and ranged from 7.8 months in the “other” cohort to 29.2 months in the salivary cohort. Median DOR was 13.1 months (95% CI, 7.3–30.5), ranging from 6.4 months in the lung cohort to 18.4 months in the “other” cohort. Conclusions: T-DM1 demonstrated heterogenous efficacy among HER2-amplified tumor types, with promising response and outcomes among patients with salivary gland cancer.